Amoebicidal, anti-adhesive, and low-cytotoxic effects of Mangifera indica L. leaf extract against ocular Acanthamoeba spp.: First evidence supporting plant-based therapeutic potential - Mendonça, Diana; Tabo, Hazel A.; Chimplee, Siriphorn; Oliveira, Sónia M. R.; Kwankaew, Pattamaporn; Girol, Ana Paula [UNESP]; Dungca, Julieta Z.; Sulaiman, Mazdida; Bhassu, Subha; Nawaz, Muhammad; Wilairatana, Polrat; Wiart, Christophe; et al. (Veterinary World, 2025)
Background and Aim: Acanthamoeba spp. is free-living protozoa capable of causing severe infections, notably Acanthamoeba keratitis, which is difficult to manage due to cyst resistance and the cytotoxicity of current treatments. Plant-derived compounds represent a promising alternative strategy. This study investigated the amoebicidal, anti-adhesive, and cytotoxic properties of Mangifera indica L. (mango) leaf extract against ocularly relevant Acanthamoeba spp. Materials and Methods: Crude ethanolic leaf extract of M. indica was prepared and evaluated against Acanthamoeba polyphaga American Type Culture Collection (ATCC) 30461 and Acanthamoeba castellanii ATCC 50739. Minimum inhibitory concentration (MIC) and minimum parasiticidal concentration were determined for trophozoites and cysts. Morphological changes were analyzed by scanning electron microscopy (SEM). Anti-adhesion assays were conducted using polystyrene surfaces, with a commercial multipurpose contact lens (CL) solution as a control. Cytotoxicity was tested in Vero cells using the 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide assay to establish the minimum cytotoxic concentration. Results: The extract inhibited trophozoite growth at 2 mg/mL and demonstrated cysticidal activity at 4 mg/mL for A. polyphaga and 32 mg/mL for A. castellanii. SEM revealed disruption of trophozoite morphology, loss of acanthopodia, and surface perforations in cysts. At MIC levels, adhesion was reduced by >70%, and even at 1/8 MIC, inhibition remained above 50%, comparable to a commercial multipurpose solution. Cytotoxicity assessment showed >80% Vero cell viability at 0.125 mg/mL, indicating a favorable therapeutic window. Conclusion: This is the first report demonstrating amoebicidal and anti-adhesive effects of M. indica L. leaf extract against ocular Acanthamoeba species. The dual trophozoiticidal and anti-adhesive actions, combined with low cytotoxicity, highlight its potential for development as a plant-based therapeutic agent, particularly in ocular formulations or CL disinfectants. Future work should focus on phytochemical isolation, mechanistic studies, and novel delivery systems to enhance efficacy and safety. Keywords: Acanthamoeba, amoebicidal activity, anti-adhesion, cytotoxicity, Mangifera indica L., ocular infection.